Pharmacodynamics of Echinocandins against Candida glabrata: Requirement for Dosage Escalation To Achieve Maximal Antifungal Activity in Neutropenic Hosts - Howard, Susan J. (American Society for Microbiology, 2011)
Candida glabrata is a leading cause of disseminated candidiasis. The echinocandins are increasingly used as first-line agents for the treatment of patients with this syndrome, although the optimal regimen for the treatment of invasive Candida glabrata infections in neutropenic patients is not known. We studied the pharmacokinetics (PK) and pharmacodynamics (PD) of micafungin, anidulafungin, and caspofungin in a neutropenic murine model of disseminated Candida glabrata infection to gain further insight into optimal therapeutic options for patients with this syndrome. A mathematical model was fitted to the data and used to bridge the experimental results to humans. The intravenous inoculation of Candida glabrata in mice was followed by logarithmic growth throughout the experimental period (101 h). A dose-dependent decline in fungal burden was observed following the administration of 0.1 to 20 mg/kg of body weight every 24 h for all three agents. The exposure-response relationships for each drug partitioned into distinct fungistatic and fungicidal components of activity. Surprisingly, the average human drug exposures following currently licensed regimens were predicted to result in a fungistatic antifungal effect. Higher human dosages of all three echinocandins are required to induce fungicidal effects in neutropenic hosts.